ANALISIS DAN PEMBAHASAN PENERAPAN RISK MANAGEMENT UNTUK MEMINIMALISIR KERUGIAN KEGIATAN PENGIRIMAN PADA PT DIVA SEMESTA TRANSINDO DI BIDANG JASA EKSPEDISI DI SURABAYA - Devina Agustin Febriana; Ria Sandra Alimbudiono (Perpustakaan Universitas Surabaya, 2018)
Abstract – This study aims to be aware of the risk of anything contained in the company and how the risk assessment is included into low risk, medium risk, or high risk. Thus it can assist management in making appropriate risk management actions to reduce the likelihood of risks and negative impact of the existing risks. This research uses qualitative approach that is explanatory research by using interview method, observation, and document analysis. The results obtained are 2 risk that the author included into low risk, 2 risk included into medium risk and 2 risk included into high risk, where all of the risks that need to be managed by using the concept of Risk Management so it can reduce the loss of the freight activities and support the goals of the business.